PENGARUH DOSIS PUPUK SP-36 DAN PUPUK ORGANIK SEMANGGI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG TANAH (Arachis hypogea L.) VARIETAS HypoMa 1 - Puput Laila; Supriyono . (Universitas Islam Kadiri, 2017)
Peanut (Arachis hypogaea L.) is one of the legume plants that have been known and cultivated in Indonesia. To increase the production of peanuts which fertilization. The purpose of this research is to know the effect of interaction dose of SP-36 fertilizer and organic fertilizer “Semanggi” to growth and production peanut varieties HypoMa 1. The research was conducted in Gesikan Village, Pakel District, Tulungagung Regency. The design used was Randomized Block Design (RAK) with two factors and repeated three times. From result research, there is noeffect dose of SP-36 fertilizer and organic fertilizer “Semanggi” to growth and production of peanut (Arachis hypogea L.) varietiesHypoMa 1.